Utilization of NCCMERP Index to Assess and Categorize Medication Discrepancies among Pediatric Patients: A Hospital Based Epileptic Cohort Study - Patil, Vivek Nilkanth; Wali, Shashikala Chanmallappa; Gudhoor, Manjula; Kini, Pratiksha N; Ganachari, Madiwalayya Shivakantayya; Byakod, Vishwa Rajakumar (International Journal of Pharmaceutical Investigation, 2026)
Background Recurrent seizures characterize epilepsy, affecting 50 million globally, with 12 million in India. Prevalence rates in North India are 6.99 per 1,000 in rural areas and 5.48 in urban areas. Medication errors pose significant risks, necessitating improved pediatric medication reconciliation to enhance treatment outcomes Objectives This study aimed to assess medication discrepancies and their severity using the NCCMERP scale in pediatric patients with epilepsy. Materials and Methods The study aimed to identify and assess the severity of medication discrepancies in a cohort of 110 pediatric epilepsy patients at a tertiary care hospital, and then intervene to address the discrepancies. Results This study screened 247 pediatric epilepsy patients, recruiting 123 eligible participants, with 110 completing a follow-up. Findings revealed a male predominance (70.90%) and diverse socio-economic backgrounds. Common medication discrepancies included drug omissions 38(46.9%) and non-adherence 16(19.73%), emphasizing the need for improved management strategies to enhance patient safety and treatment outcomes in pediatric epilepsy care. Conclusion Study identifies key challenges in pediatric epilepsy management, highlighting the need for tailored treatment approaches, improved medication adherence, and enhanced communication among healthcare providers and increased parental involvement for better outcomes.
Keywords: Epileptic; Pediatric; Medication Discrepancies; Patient Education